Trends in deaths following drug use in England before, during, and after the COVID-19 lockdowns - Sekeris, Athanasios; Algahtani, Thikra; Aldabergenov, Daniyar; Rock, Kirsten L.; Auwal, Fatima; Aldewaissan, Farah; Williams, Bryn D.; Kalk, Nicola J.; Copeland, Caroline S. (Frontiers in Public Health, 2023)
In March 2020 the UK Government introduced measures to reduce the impact of the COVID-19 virus. This included 'lockdowns' to limit human interaction and travel. Whilst this significantly changed the lives of everyone, people who use drugs were further impacted by changes in the drugs market, and their interaction with health, harm minimisation, and social care support services. This study uses clinical and toxicological data collected from coroners to understand how the COVID-19 pandemic affected deaths related to drug use in England, with the aim of informing how future health and social care strategy can be best adapted to prevent fatal drug overdoses in future emergency scenarios. We found that whilst the overall number of deaths following drug use did not change in the pandemic, the proportion of people who died at home vs in hospital significantly increased, as did methadone related deaths, whilst heroin/morphine-related deaths decreased. The proportion of deaths following drug use concluded as suicide also increased, as did the proportion of deaths due to antidepressant use. Considering these findings, harm-reduction strategies against the risk of lone drug use and improving concurrent provision of substance misuse and mental health support may mitigate such harms in a future emergency.